Numerical Solution of Heat Equation with Singular Robin Boundary Condition - Lozada-Cruz, German; Rubio-Mercedes, Cosme Eustaquio; Rodrigues-Ribeiro, Junior (Trends in Computational and Applied Mathematics, 2018)
In this work we study the numerical solution of one-dimensional heat diffusion equation with a small positive parameter subject to Robin boundary conditions. The simulations examples lead us to conclude that the numerical solutions of the differential equation with Robin boundary condition are very close of the analytic solution of the problem with homogeneous Dirichlet boundary conditions when tends to zero